Hubungan Mode Adaptif Konsep Diri Berbasis Teori Callista Roy dengan Kemampuan Interaksi Sosial Anak Tunagrahita di SLB-C TPA Kabupaten Jember - Zuhrotul Rofiqoh; Nurfika Asmaningrum; Dodi Wijaya (Pustaka Kesehatan, 2018)
Self concept is one of adaptive modes based on Callista Roy’s theory which very important formental deficiency influence integrity of mental in practice to had a good social interaction. The kind ofthis research is descriptive analytic by using study cross sectional. Method of collecting samplesusing total sampling and total of samples got are 35 respondents. Data was analyzed by chi-squareand the result of statistical test shows point p=0.000. Ha is accepted if Ho is rejected in which Ho isrejected if the point is p ≤ α, 0,000 ≤ 0,05. The result of the statistic analysis is that there is significantcorrelation between adaptive modes: self concept based on Callista Roy’s theory and socialinteraction abilities to mental retardation children on SLB-C TPA at Jember Regency. OR (26.00),that means the respondents who had a positive self concept have 26.00 possibility to be had a goodsocial interaction abilities. The result of the research is positive self concept with good socialinteraction ability about 80%. Suggests for nursing in community to involve and increase their rolemodel as educator and care giver in attempt to share information by doing a counseling.Keywords: self concept, social interaction, mental retardation